PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN, KOMPENSASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - Ernawati Ernawati; Ella Anastasya Sinambela; Rahayu Mardikaningsih; Didit Darmawan (ITB AAS INDONESIA Surakarta, 2021)
The existence of business competition, every company needs to improve employee performance so that company performance increases. Companies need to pay attention to every thing that is indicated to improve employee performance. This study aims to determine the role of organizational culture, leadership, compensation, and organizational commitment on employee performance. This research was conducted on 53 respondents who are employees of traditional herbal medicine factories in Sidoarjo. The analysis technique is linear regression. The research findings state that organizational culture and organizational commitment partially affect employee performance. The leadership variable also partially shows a significant effect on employee performance. Compensation has a significant effect on employee performance. This study also found that all independent variables simultaneously had a significant effect on employee performance. Keywords : Organizational Culture, Leadership, Compensation, Organizational Commitment.